2024
DOI: 10.1002/ange.202400658
|View full text |Cite
|
Sign up to set email alerts
|

Rechargeable Afterglow Nanotorches for In Vivo Tracing of Cell‐Based Microrobots

Gongcheng Ma,
Musa Dirak,
Zhongke Liu
et al.

Abstract: As one of the self‐luminescence imaging approaches that require pre‐illumination instead of real‐time light excitation, afterglow luminescence imaging has attracted increasing enthusiasm to circumvent tissue autofluorescence. In this work, we developed organic afterglow luminescent nanoprobe (nanotorch), which could emit persistent luminescence more than 10 days upon single light excitation. More importantly, the nanotorch could be remote charged by 660 nm light in a non‐invasive manner, which showed great pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…As an FDA (Food and Drug Administration)-approved drug, methylene blue has been used as a NIR contrast agent for the evaluation of the renal function of the animal or the activatable NIR probe by adding a carbamate caging group on the 10-N position. In this work, we found that methylene blue could quickly be transformed into NIR-II emissive AIEgens through the protonation of methylene blue in extreme acidic solution. Moreover, the NIR-II emissive AIEgens could be generated in situ in a hyperchlorhydria stomach, which could be used for studying hyperchlorhydria related disease.…”
mentioning
confidence: 86%
“…As an FDA (Food and Drug Administration)-approved drug, methylene blue has been used as a NIR contrast agent for the evaluation of the renal function of the animal or the activatable NIR probe by adding a carbamate caging group on the 10-N position. In this work, we found that methylene blue could quickly be transformed into NIR-II emissive AIEgens through the protonation of methylene blue in extreme acidic solution. Moreover, the NIR-II emissive AIEgens could be generated in situ in a hyperchlorhydria stomach, which could be used for studying hyperchlorhydria related disease.…”
mentioning
confidence: 86%